Effects of Classical Breathing Exercises on Posture, Spinal and Chest Mobility among Female University Students Compared to Currently Popular Training Programs - Csepregi, Éva; Gyurcsik, Zsuzsanna; Veres-Balajti, Ilona; Nagy, Attila Csaba; Szekanecz, Zoltán; Szántó, Sándor (International journal of environmental research and public health, 2022)
Worldwide, university students’ physical health and posture are declining due to a sedentary lifestyle. The aim of our study was to evaluate the effectiveness of physiotherapeutic breathing exercises on posture and spinal mobility among healthy female university students compared to other training methods. Sixty-one female students of the University of Debrecen were assigned to breathing exercise (BE; n = 15), yoga (Y; n = 16), Pilates (P; n = 15) programmes and interval-training (IT; n = 15). Each training session lasted one hour, performed twice a week for 7 weeks. Students were assessed using standardized clinical tests. All programmes resulted in significant improvement in chest expansion. Results of Schober’s test showed substantial improvement using BE (p < 0.05), Y, P (p ≤ 0.01) programmes. Significant changes in occiput-to-wall distance (Y, P p ≤ 0.01) (BE p ≤ 0.001) were observed in three groups except the IT group. Fingertip-to-floor test (Y, P p < 0.05) results showed significant changes in two groups. The most outstanding effects on lateral flexion were achieved using BE (right, left p ≤ 0.001) programme. A comparison with results achieved using yoga and Pilates revealed that the physiotherapeutic breathing exercise programme is an equally effective method to significantly improve spinal mobility and correct postural problems in healthy young women.